Laboratory exercises in organismal and molecular microbiology - Alexander, Steve K. (McGraw-Hill, 2004)
A modern general microbiology laboratory manual that combines the procedural details of a laboratory manual with the photographic support of a laboratory atlas. The 46 class-tested laboratory experiments are divided into 9 specialty areas, and the extensive four-color illustration program includes 220 photos and micrographs plus 150 line drawings.